Effect of Lallemantia royleana Seeds Extract in Liver Functions Enzymes Levels and in some Mice Activity Features Treated with Rifadin drug - Al-Barram, Mohammed F. A.; Al-Asady, Zainab T. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was aimed to investigate the role of crud alcoholic extract of Lallemantia royleana seeds in reducing the hepatotoxicity and side effect of rifadin drug in liver.                      The animals (40 mice) were divided into four groups, the first group was treated with normal saline (0.9%) for 28 days as a control and the second group was treated with rifadin (1.5 mg/kg/day) for 28 days and third group was treated with acoholic extract of Lallemantia royleana seeds (1% w/v) for 28 days, while the forth group was treated with alcoholic extract of seeds alone for 5 days and with alcoholic extract and rifadin for 28 days, so the total period of this group is 33 days. The blood samples ware collected to measure the liver function enzymes represented by Alkalin phosphatse (ALP), Alanine transaminase (ALT), Aspartate Transaminase (AST), and the animals in experimental groups were observed to investigate the animals activity changes in groups after treated with drug and extract.                                       Significant increases (P